Clinical Impact of Early CT Scans after Lateral Skull‐Base Surgery. Issue 5 (5th September 2013) - Jiang, Zi Yang; Allen, Kyle; Kutz, J. Walter; Isaacson, Brandon
Abstract : Objective: To determine the frequency and clinical significance of abnormalities on postoperative computerized tomography (CT) scans performed within 24 hours after lateral skull base surgery. Study Design: Case series with chart review. Setting: Inpatient tertiary care hospital. Methods: Adult patients undergoing lateral skull base surgery were identified using CPT code search from January 2010 to January 2013. Patient demographics, type of skull base lesion, surgical approach, length of operation, time between end of the surgery and CT scan, CT scan findings, and patients' postsurgical neurologic status were collected. Results: One hundred and seventy‐two patients were identified who had a postoperative CT scan after lateral skull base surgery. Diagnoses included schwannoma (95), cerebrospinal fluid fistula (29), middle fossa encephaloceles (9), meningioma (13), superior semicircular canal dehiscence (12), and other disease processes (14). The approaches were middle fossa (64), translabyrinthine (70), suboccipital (17), infratemporal (8), and combined/other (13). Mild pneumocephalus was almost always found, along with mild extra‐axial blood. Twenty‐four patients had significant mass effect found on CT scan, but this was present preoperatively. Three patients had a mild subdural without neurological decline. No patient suffered any clinically significant neurological decline, although 5 patients reported finger numbness that resolved spontaneously and 2 patients had confusion in the immediate postoperative period. Conclusion: Clinically significant abnormalities on immediate postoperative CT scans were rare, as were cases of neurological decline. Further prospective studies could determine a more cost‐effective algorithm for routine use of postoperative imaging.